Recent molecular and therapeutic advances in B‐cell non‐Hodgkin lymphoma in children. (21st March 2016) - Giulino‐Roth, Lisa; Goldman, Stanton
Summary: Paediatric B‐cell non‐Hodgkin lymphoma (B‐NHL) compromises a heterogeneous group of histological entities of which Burkitt lymphoma is the most common. In resource‐rich countries, the expected cure rate is in excess of 85% with application of risk‐adapted short intensive chemotherapy. In recent years, large paediatric cooperative group trials have sought to improve upon outcomes by decreasing the intensity of cytotoxic treatment as well as introducing targeted therapies, such as rituximab. These efforts have resulted in excellent outcomes, however there remains a group of high‐risk patients for whom novel treatment approaches are needed. In this review, we will summarize the recent paediatric clinical trials in B‐NHL as well as compare treatment approaches across the major cooperative groups. We will also highlight our current understanding of the molecular biology of paediatric B‐NHL with a focus on how this may help guide future rational targeted therapy.